Cost-effective strategies for CAR-T cell therapy manufacturing - Luiza Abdo; Leonardo Ribeiro Batista-Silva; Martín Hernán Bonamino (Molecular Therapy: Oncology)
CAR-T cell therapy has revolutionized cancer treatment, with approvals for conditions like acute B-leukemia, large B cell lymphoma (LBCL), follicular lymphoma (FL), mantle cell lymphoma (MCL), and multiple myeloma. However, its high costs limit accessibility. Key factors driving these costs include the need for personalized, autologous treatments, transportation to specialized facilities, reliance on viral vectors requiring advanced laboratories, and lengthy cell expansion processes. To address these challenges, alternative strategies aim to simplify and reduce production complexity. Non-viral vectors, such as Sleeping Beauty, piggyBac, and CRISPR, delivered via nanoparticles or electroporation, present promising solutions. These methods could streamline manufacturing, eliminate the need for viral vectors, and reduce associated costs. Furthermore, shortening cell expansion periods and optimizing protocols could significantly accelerate production. An emerging approach involves using genetically edited T cells from healthy donors to create universal CAR-T products capable of treating multiple patients. Finally, decentralized point-of-care (POC) manufacturing of CAR-T cells minimize logistical expenses, eliminating the need for complex infrastructure, and enabling localized production closer to patients. This innovative strategy holds potential for broadening access and reducing costs, representing a step toward democratizing CAR-T therapy. Combined, these advances could make this groundbreaking treatment more feasible for healthcare systems worldwide.